Approximation of solutions of boundary value problems for integro-differential equations of the neutral type using a spline function method - Cherevko, Igor; Dorosh, Andrii; Haiuk, Ivan; Pertsov, Andriy (My University, 2022)
Boundary value problems for nonlinear integro-differential equations of the neutral type are investigated. A scheme for approximating the boundary value problem solution using cubic splines of defect two is proposed and substantiated. A model example illustrating the proposed approximation scheme is considered.
Keywords: Boundary value problem; Neutral type; Cubic splines